Advances in artificial intelligence and soft computing : 14th Mexican International Conference on Artificial Intelligence, MICAI 2015, Cuernavaca, Morelos, Mexico, October 25-31, 2015, proceedings, part I /: 14th Mexican International Conference on Artificial Intelligence, MICAI 2015, Cuernavaca, Morelos, Mexico, October 25-31, 2015, proceedings, part I. (2015) - Unknown
No abstract available